2021
DOI: 10.1002/uog.23568
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac function at 19–23 weeks' gestation in prediction of pre‐eclampsia

Abstract: What are the novel findings of this work?Maternal cardiovascular indices at 19-23 weeks' gestation are affected significantly by maternal demographic characteristics and elements of medical history known to be associated with an increased risk for subsequent development of pre-eclampsia (PE). After adjustment for these maternal factors, only peripheral vascular resistance was affected by PE. What are the clinical implications of this work?Assessment of maternal cardiovascular function provides information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The study population of 2853 pregnancies contained 199 (7.0%) that developed GDM; GDM was diagnosed at < 20 weeks (median, 12 weeks) in 39 (19.6%) cases, at 20–30 weeks (median, 29 weeks) in 133 (66.8%) cases and at ≥ 31 weeks (median, 33 weeks) in 27 (13.6%) cases. The same population was used for our previous studies investigating the value of ophthalmic artery Doppler 16 and maternal cardiovascular indices 14 in the prediction of pre‐eclampsia and on the relationship between ophthalmic artery Doppler and maternal cardiovascular function 17 . Maternal and pregnancy characteristics of the study population are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population of 2853 pregnancies contained 199 (7.0%) that developed GDM; GDM was diagnosed at < 20 weeks (median, 12 weeks) in 39 (19.6%) cases, at 20–30 weeks (median, 29 weeks) in 133 (66.8%) cases and at ≥ 31 weeks (median, 33 weeks) in 27 (13.6%) cases. The same population was used for our previous studies investigating the value of ophthalmic artery Doppler 16 and maternal cardiovascular indices 14 in the prediction of pre‐eclampsia and on the relationship between ophthalmic artery Doppler and maternal cardiovascular function 17 . Maternal and pregnancy characteristics of the study population are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The following eight cardiovascular indices were examined: E/A ratio; E/e′ ratio; myocardial performance index; global longitudinal systolic strain; left ventricular ejection fraction; peripheral vascular resistance; left ventricular cardiac output; and left ventricular mass indexed for body surface area. The measured values of cardiovascular indices were converted to multiples of the median (MoM) or difference from the median (delta) values, where appropriate, to remove the effects of maternal demographic characteristics and elements from the medical and obstetric history, as described previously; these factors included gestational age, maternal age, weight, height, racial origin, heart rate, method of conception and history of chronic hypertension or antiphospholipid syndrome 14 . We found no significant contribution from family history of diabetes mellitus or history of GDM in a previous pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Using speckle tracking echocardiography, the group reported that left ventricle hypertrophy and concentric geometry is the strongest independent predictor of complications in the subsequent pregnancy. Concentric geometry appears in early complications, whereas eccentric hypertrophy appears in late complications [65]. With regards to diastolic function, it seems to be an independent predictor of complications [65,66].…”
Section: Speckle Tracking Echocardiography In Preeclampsia Chronic Hy...mentioning
confidence: 91%
“…Concentric geometry appears in early complications, whereas eccentric hypertrophy appears in late complications [65]. With regards to diastolic function, it seems to be an independent predictor of complications [65,66].…”
Section: Speckle Tracking Echocardiography In Preeclampsia Chronic Hy...mentioning
confidence: 91%
See 1 more Smart Citation